Online Bible Study During a Pandemic: Challenges, Solutions, and Opportunities - Tomson Saut Parulian Lumbantobing; Priyantoro Widodo (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2021)
The government's decision to implement social distancing during the Covid-19 pandemic has changed the concept, method, and design of education. Teaching and learning activities that were originally face-to-face are now being replaced by learning using electronic media (e-learning) or online learning systems. Like formal education, Covid-19 has also changed the concept, method, and design of Bible studies carried out by churches, church institutions, and theological schools. The research aims to obtain information about the problems that hinder online Bible studies carried out by churches, church organizations, and theological schools during the Covid-19 pandemic and find solutions. The research belongs to the descriptive qualitative variety. The results of the study show that churches, church organizations, theological schools, including Christians, are not ready to carry out online Bible studies during the Covid-19 pandemic. Some of the problems that cause obstacles to online Bible learning are the availability of facilities such as networks, quotas, smartphones, or laptops, the skills of implementers and participants to use online learning applications, and the lack of good preparation from implementers including teachers. The solution to overcome this is the need for churches, church institutions, and theological schools to allocate funds for the procurement of online Bible study facilities, good preparation, especially from implementers and teachers, gathering a limited number of participants in places that have good internet access, and when buying quotas for participants who are economically disadvantaged.